FRI0395 Digital ulcers as a "sentinel" sign for early internal organ involvement in very early systemic sclerosis: evidence from a single vedoss/eustar centre. (23rd January 2014) - Bruni, C.; Guiducci, S.; Bellando-Randone, S.; Lepri, G.; Braschi, F.; Fiori, G.; Bartoli, F.; Matucci-Cerinic, M.
Abstract : Objectives: Evaluation of the presence of digital lesions [1 ] in patients with diagnosis of very early systemic sclerosis (VEDOSS) [2 ] and of their correlation with clinical, laboratory and imaging parameters. Methods: 110 VEDOSS patients were investigated for presence of digital pitting scar, calcinosis, digital ulcers (DUs), necrosis or gangrene, nailfold videocapillaroscopic abnormalities, disease specific autoantibodies (anti-centromere and anti-topoisomerase I) and internal organ involvement (chest HRCT, pulmonary function tests with DLCO evaluation, oesophagealmanometry, Holter ECG, cardiac Doppler US, renal arteries Doppler US) [3 ]. Results: 4 patients reported a history of digital pitting scars, 16 patients presented active DU and 14/16 also reported a history of previous DUs. Other 9 patients reported a history of DUs only. Both the history and the presence of DUs showed statistically significant correlation with esophageal manometry only (analyzed through IBM SPSS Statistics version 19, using Spearman's Rho test:ρ=0, 681 &ρ=0, 633 respectively, p < 0, 05). Clustering patients according to the presence of internal organ involvement, DUs were observed in VEDOSS patients with internal organ involvementbut not in those without organ involvement. Image/graph: Conclusions: DUs are already present in VEDOSS patients and correlate with esophageal involvement [4 ]. DU may be considered as a sentinel sign for the presence of early organ involvement, meaning the evolution from thevery early to the early phase of systemic sclerosis [5 ]. References: Amanzi L et al. Digital ulcers in scleroderma:staging, characteristics and sub-setting through observation of 1614 digital lesions. Rheumatology (Oxford).2010 ;49:1374-82. Avouac J et al, "Preliminary criteria for the very early diagnosis of systemic sclerosis: results of a Delphi Consensus Study from EULAR Scleroderma Trials and Research Group", Ann Rheum Dis. 2011 Mar;70:476-81. Czirjak L, Matucci Cerinic M: Beyond Raynaud's phenomenon hides a very early systemic sclerosis: the assessment of organ involvement is always mandatory. Rheumatology 2011;50:250-1 Lepri G et al: Evidence for Esophageal and anorectal involvement in patients with very early diagnosis of systemic sclerosis (VEDOSS):report from a single EUSTAR centre. (Submitted) Matucci Cerinic M et al: Very early versus early disease: the evolving definition of the many faces of Systemic Sclerosis Ann Rheum Dis; 2012 Nov 23 Disclosure of Interest : None Declared